Respuesta :
Answer:
when you simplify the answer is -0.91113026
Step-by-step explanation:
Answer:
[tex]\cos(12)\cos(-3)-\sin(12)\sin(-3)=0.98[/tex]
Step-by-step explanation:
Given : Expression [tex]\cos(12)\cos(-3)-\sin(12)\sin(-3)[/tex]
To find : Simplify the expression ?
Solution :
Expression [tex]\cos(12)\cos(-3)-\sin(12)\sin(-3)[/tex]
We know the trigonometry identity,
[tex]\cos A\cos B-\sin A\sin B=\cos (A+B)[/tex]
Here, A=12 and B=-3
[tex]\cos(12)\cos(-3)-\sin(12)\sin(-3)=\cos(12+(-3))[/tex]
[tex]\cos(12)\cos(-3)-\sin(12)\sin(-3)=\cos(12-3)[/tex]
[tex]\cos(12)\cos(-3)-\sin(12)\sin(-3)=\cos(9)[/tex]
From calculator, [tex]\cos 9=0.98[/tex] in degrees.
Therefore, [tex]\cos(12)\cos(-3)-\sin(12)\sin(-3)=0.98[/tex]